The Mode of Action of CY216 and CY222 in Plasma - Béguin, Suzette; Wielders, Simone; Lormeau, J C; Hemker, H Coenraad (Thrombosis and Haemostasis, 1992)
Three fractions of the low molecular weight heparin CY216 (fraxiparin, mean molecular weight [MMW] 5,090), with MMWs of respectively, 3,090, 4,400 and 7,910 were prepared by gel permeation chromatography. From CY222 (MMW 3,770) as well as from CY216 and its three fractions the material with high affinity to antithrombin III (AT III) was obtained by chromatography on immobilised AT III. The molecular weight distribution of each of the ten preparations thus obtained was determined by high performance liquid chromatography, while the content of AT III binding material was determined by stoichiometric titration of AT III, monitored by intrinsic fluorescence enhancement.We measured the effect of all heparins on the decay of endogenous thrombin in plasma and on the overall generation of thrombin in plasma, triggered via the extrinsic or via the intrinsic pathway. From these data we calculated the time course of prothrombin conversion, i. e. the course of factor Xa activity as expressed by prothrombinase activity.It was found that in platelet-poor plasma the anticoagulant properties of the heparins are largely dependent on their antithrombin action, which is determined by their content of high affinity material with a MW of 5,400 or higher. The specific antithrombin activity of all heparins, when expressed in terms of material with high affinity to antithrombin III (HAM) with a MW >5,400 is 13.0 min-1/(μg/ml) (range 10.5-15.9). The anticoagulant potency is not influenced by the presence of low-affinity material and hardly by material with MW <5,400.In platelet-rich plasma, however, the presence of non-AT III binding material enhances the inhibition, presumably by neutralising heparin binding material originating from activated platelets. The ultra low MW fractions (<3,400) show a similar activity in PPP and in PRP.